Borg Mesch: The Role of a Culture Broker in Picturing the North - DuBois, Thomas A. (Journal of Northern Studies, 2014)
This paper examines the role of Borg Mesch (1869–1956) in the development of a nascent tourist industry in the North of Sweden. The concept of culture broker is used to clarify Mesch’s varying activities as a photographer, outfitter, and guide in relation to two different clienteles: Swedes from the south of the country and international tourists from England and elsewhere. The history of Svenska Turistföreningen (the Swedish Tourist Association) in facilitating tourist activities in northern regions is described.